Book review: Rajan Gurukkal and Varier Raghava, History of Kerala: Prehistoric to the Present. (September 2019) - Varghese, Rachel A.
Rajan Gurukkal and Varier Raghava, History of Kerala: Prehistoric to the Present . Hyderabad, India: Orient BlackSwan, 2018, 366 pp., ₹315, ISBN: 978-93-5287-380-7. (Paperback) .